2014
DOI: 10.1186/s13058-014-0492-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of common breast cancer susceptibility alleles with risk of breast cancer subtypes in BRCA1 and BRCA2 mutation carriers

Abstract: IntroductionMore than 70 common alleles are known to be involved in breast cancer (BC) susceptibility, and several exhibit significant heterogeneity in their associations with different BC subtypes. Although there are differences in the association patterns between BRCA1 and BRCA2 mutation carriers and the general population for several loci, no study has comprehensively evaluated the associations of all known BC susceptibility alleles with risk of BC subtypes in BRCA1 and BRCA2 carriers.MethodsWe used data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 23 publications
(46 reference statements)
2
63
0
Order By: Relevance
“…A systematic evaluation of the associations of 74 known breast cancer susceptibility alleles found that their associations with ER-positive breast cancer for BRCA1 and BRCA2 mutation carriers were more consistent with the associations of these SNPs with ER-positive breast cancer in the general population. Furthermore, the associations of these SNPs with ER-negative breast cancer for BRCA1 and BRCA2 mutation carriers were more consistent with the associations of the SNPs with ER-negative breast cancer in the general population (Kuchenbaecker et al 2014). Similarly, common variants associated with the risk of serous ovarian cancer in the general population are associated with overall ovarian cancer risk for carriers of mutations in both genes (approximately two-thirds of whom develop serous disease) (Mavaddat et al 2012).…”
Section: Genetic Modifierssupporting
confidence: 59%
See 3 more Smart Citations
“…A systematic evaluation of the associations of 74 known breast cancer susceptibility alleles found that their associations with ER-positive breast cancer for BRCA1 and BRCA2 mutation carriers were more consistent with the associations of these SNPs with ER-positive breast cancer in the general population. Furthermore, the associations of these SNPs with ER-negative breast cancer for BRCA1 and BRCA2 mutation carriers were more consistent with the associations of the SNPs with ER-negative breast cancer in the general population (Kuchenbaecker et al 2014). Similarly, common variants associated with the risk of serous ovarian cancer in the general population are associated with overall ovarian cancer risk for carriers of mutations in both genes (approximately two-thirds of whom develop serous disease) (Mavaddat et al 2012).…”
Section: Genetic Modifierssupporting
confidence: 59%
“…In this context, within CIMBA, four approaches have been applied to identify loci associated with breast and ovarian cancer for mutation carriers: (i) GWAS for breast and ovarian cancer specifically performed in samples of BRCA1 and BRCA2 mutation carriers (Antoniou et al 2010b, Gaudet et al 2013; (ii) association 23:10 studies to assess common breast and ovarian cancer susceptibility alleles identified in the general population as potential modifiers of risk for mutation carriers (Antoniou et al 2008b, Kuchenbaecker et al 2014; (iii) meta-analyses of GWAS performed in BRCA1 and BRCA2 mutation carriers with GWAS of related phenotypes in the general population (for example, combining studies of breast cancer risk for BRCA1 mutation carriers with those of oestrogen receptor-negative breast cancer in general population or studies of ovarian cancer risk for BRCA1 and BRCA2 mutation carriers with GWAS of serous ovarian cancer in the general population) (Kuchenbaecker et al 2015, Couch et al 2016; and iv) finescale mapping of risk-modifying loci identified through GWAS approaches to fully characterise the associations with all genetic variants at these loci (Bojesen et al 2013, Dunning et al 2016, Lawrenson et al 2016.…”
Section: Genetic Modifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients were diagnosed with invasive breast cancer at the University of British Columbia hospitals between 1989 and 2002 and have been previously described 44 . A detailed description of the validation set consisting of 3,992 breast cancer patients has been previously published 45,46 . In brief, newly diagnosed invasive breast cancers from centres across the province of British Columbia performing breast cancer excision surgery, referred to the British Columbia Cancer Agency (BCCA) between 1986 and 1992 and for which both blocks from a central estrogen receptor testing laboratory and detailed clinico-pathologic, treatment and outcome data collected by the BCCA Breast Cancer Outcomes Unit were available were assembled into 17 single core tissue microarray blocks.…”
Section: Methodsmentioning
confidence: 99%